Protective effects of quercetin against cisplatin induced urogenital organ toxicity - ERCAN, FERİHA; ŞENER, GÖKSEL; ŞENER, TARIK EMRE (MARMARA UNIV, 2020)
Cisplatin is a chemotherapeutic agent that is the first to enter treatment from organic platinum-derived drugs. Nephrotoxicity and cytotoxicity are major factors that limit its use. The aim of the study is to investigate the possible protective effects of quercetin against cisplatin-induced urogenital organ toxicity. In our study, Sprague Dawley four month old male rats were divided into 4 groups; control + saline (SF), control + quercetin (20 mg/kg for 21 days), cisplatin (7 mg/kg as a single dose) + SF and cisplatin + quercetin groups. After decapitation, the kidney, bladder, testis and corpus cavernosum tissue samples were taken to analyze caspase-3, an index of apoptosis, and oxidative stress parameters such as malondialdehyde (MDA), gluta-thione (GSH), and 8-hydroxy-2'-deoxyguanosine (8-OHdG). Furthermore, tissues were also examined histologically. Cisplatin caused significant increases in MDA and 8-OHdG levels, demonstrating increases in lipid peroxidation and oxidative DNA damage, respectively, in all tissues. In parallel with the oxidant stress increase, the endogenous strong antioxidant GSH levels were decreased. Caspase activity and caspase 3 expressions, which we measured as an indicator of apoptosis, increased significantly with cisplatin treatment. On the other hand, treatment with quercetin, a powerful antioxidant flavonoid, reversed these changes. Histological findings also demonstrated well-preserved tissues due to quercetin treatment. In conclusion, our results suggested that quercetin, when given with cisplatin, can be protective against the chemotherapeutic induced toxicity and thus provide therapeutic benefit.
Keywords: Cisplatin; oxidative stress; quercetin; bladder; kidney; testis; corpus cavernosum; INJURY; NEPHROTOXICITY; MELATONIN; STRESS